Evaluating the Efficacy of Cueing Strategies versus Walking Aids in Parkinson’s Disease: An Interventional Study - Sharki Rawat; Jyoti Balyan; Sonia (Journal of Clinical and Diagnostic Research)
Introduction: Parkinson’s Disease (PD) is a neurodegenerative disorder that affects both motor and non motor brain pathways. It is the world’s second most common neurodegenerative illness, with an increasing incidence. The PD results in slow movement, tremors, involuntary movements, difficulty walking, and imbalance. The focus of physical therapy treatment is to improve balance, postural stability, and walking. The use of walking aids promotes stability, and cues help individuals with PD improve their stride. External cues provide temporal or spatial inputs related to the initiation and cessation of motor activities. Aim: To evaluate the effectiveness of cueing strategies and walking aids in patients with PD and their impact on gait and balance. Materials and Methods: The interventional study was carried out at Adarsh Chander Medicare Centre, Rohtak, Haryana, India for six weeks, from March 2023 to May 2023. The participants were divided into two groups, A and B, with 30 participants in each group. Participants in Group A were trained with walking aids, while those in Group B were trained with cueing strategies. Pre- and post-training assessments were conducted using the Unified Parkinson’s Disease Rating Scale (UPDRS), the Berg Balance Scale (BBS), and a measuring tape to evaluate step length, stride length, balance, and gait. Data analysis was performed using Statistical Package for Social Sciences (SPSS) version 20.0. Mean values were compared using a t-test (for two groups). A p-value of less than 0.05 was considered statistically significant. Results: The mean age of Group A was 67.60±4.80 years, while the mean age of Group B was 69.40±5.63 years. The pretraining UPDRS reading for Group A was 152.43±12.55, while for Group B, it was 153.00±15.14 (p=0.87). The post-training reading for Group A was 144.27±12.43, and for Group B, it was 140.43±15.07 (p=0.28). The pre-training BBS reading for Group A was 28.20±5.68, and for Group B, it was 28.17±4.72 (p=0.98). Post-training, Group A had a reading of 32.63±5.76, and Group B had 38.80±4.35 (p=0.01). There was also a significant improvement in step and stride lengths in Group B compared to Group A. Conclusion: There was a notable enhancement in balance and gait among individuals who engaged in an exercise program across both groups. However, the group that underwent exercise training with cueing strategies exhibited more favorable outcomes compared to the group that solely used walking aids. Therefore, exercise training incorporating cueing strategies may present a promising treatment approach for individuals with PD.